Photonic textile sensing for sports and healthcare - Bradbury, James A. (2023)
The focus of this research is to develop a sensor that can be used to assess muscle performance during exercise. A novel, textile-based fibre optic sensor (TBFOS) is designed and produced to perform Near Infrared Spectroscopy (NIRS) on the thigh, to produce muscle oxygen saturation (SmO2) measurements. Design choices for this sensor are informed via a literature review, computer models and the production and use of optical phantoms. As the TBFOS requires pressure to be applied to the limb to hold the sensor in place, a fibre optic pressure sensor (FOPS) is also developed, to measure the compression applied by a textile. These technologies are both tested on volunteers using protocols designed to replicate clinical or exercise scenarios.